Systematic review and meta-analysis on the effect of contrast training on vertical jump performance. - Pagaduan, J.; Schoenfeld, B.; Pojskic, H. (Strength and Conditioning Journal, 2019)
The purpose of this article was to perform a systematic review and meta-analysis on the effect of contrast training (CT) on vertical jump performance. Thirteen of 83 studies were included for systematic review, whereas 10 studies were used for meta-analysis. Meta-analysis revealed greater countermovement jump (cmj) gains in ct than in resistance training (RT) (effect size [es] = 1.30; confidence interval [ci] = 0.31-2.30). Similarly, ct displayed higher cmj than control (es = 1.46; ci = 0.46-2.46). In conclusion, ct showed greater improvement in cmj compared with rt and con. For a video abstract of this article, see video, supplemental digital content 1, http://links.lww.com/scj/a247